2018
DOI: 10.3390/md16110424
|View full text |Cite
|
Sign up to set email alerts
|

New 9α-Hydroxy-5α,6α-epoxysterols from the Vietnamese Marine Sponge Ircinia echinata

Abstract: Chemical investigation of the methanol extract of the Vietnamese marine sponge Ircinia echinata led to the isolation of six new 9α-hydroxy-5α,6α-epoxysterols: 5α,6α-epoxycholesta-7,22(E)-dien-3β,9α-diol (1), 5α,6α-epoxycholesta-7,24(28)-dien-3β,9α-diol (2), (24R)-5α,6α-epoxy-24-ethyl-cholesta-7-en-3β,9α-diol (3), 5α,6α-epoxycholesta-7-en-3β,9α-diol (4), (24S)-5α,6α-epoxyergosta-7,22-dien-3β,9α-diol (5), and (24R)-5α,6α-epoxy-24-methyl-cholesta-7-en-3β,9α-diol (6) along with the known 5α-6α-epoxysterols: 5α,6α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also, Trinh et al. ( 2018 ), isolated six new 9α-hydroxy-5α,6α-epoxysterols from the Vietnamese marine sponge, Ircinia echinate and showed that two sterols (24 R )-5α,6α-epoxy-24-ethyl-cholesta-7-en-3β,9α-diol and 5α,6α-epoxycholesta-7-en-3β,9α-diol have cytotoxic activity against three human cancer cell lines, MCF-7, Hep-G2 and LU-1.…”
Section: Introductionmentioning
confidence: 97%
“…Also, Trinh et al. ( 2018 ), isolated six new 9α-hydroxy-5α,6α-epoxysterols from the Vietnamese marine sponge, Ircinia echinate and showed that two sterols (24 R )-5α,6α-epoxy-24-ethyl-cholesta-7-en-3β,9α-diol and 5α,6α-epoxycholesta-7-en-3β,9α-diol have cytotoxic activity against three human cancer cell lines, MCF-7, Hep-G2 and LU-1.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, marine microorganisms are being studied and are promising candidates for drug discovery in the near future [13,14]. Furthermore, challenges to the marine ecosystem were revealed when large amounts of sponge samples were collected for bioactive compound screening and pure substance isolation [15][16][17]. It becomes a threat to the single species when the understanding of sponge diversity and its distribution in the Vietnamese sea is limited.…”
Section: Introductionmentioning
confidence: 99%